THE ROLE OF THE ZALORA E-COMMERCE APPLICATION IN INDONESIA BASED ON CONSUMER TRUST AND SATISFACTION - Dewi Puspaningtyas Faeni; Elna Rosdiana Putri (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Examining how well the Zalora application works is the aim of this research. The literature review and qualitative research methodology used in this project were taken from various sources, including but not limited to scientific articles, books, and the internet. The research revealed a number of studies related to the following topics: 1. Consumer happiness and trust in Zalora; 2. Zalora's role in consumer interests; 3. Price compliance with product quality; 4. Effectiveness of advertising in influencing consumer interest; 5. Weaknesses of the Zalora application.